HUBUNGAN HASIL BELAJAR MATA KULIAH KEWIRAU SAHAAN DENGAN MINAT BERWIRAUSAHA MAHASISWA PROGRAM STUDI TEKNIK SIPIL DAN BANGUNAN FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 478-484 , Azwar Hidayat (CIVED, 2015)
Abstract The aim of this research is to determine how strong the learning outcome among Civil Engineering Diploma degree and Building Engineering. This research is descriptive corelative that are quantitive. Populations in this research are student of Civil Engineering and Building Engineering who take entrepreneurship in academic year 2013. Populations amounts 118 peoples. Samples are taken by using Harry King and Proportional Random Sampling technique that amounted 40 peoples. This study is analyzed by using product moment correlation formula. The hypothesis of this study is that there is a relationship of learning outcomes entrepreneurship courses with interest in entrepreneurship. Based on Calculation, obtained rcount > rtable (0.818 > 0.263). These results indicate there is a significant relationship of entrepreneurship course learning outcomes in interest entrepreneurship among Civil Engineering Diploma degree and Building Engineering, and also those are belonging to strong category. Key words:Learning Outcomes, Entrepreneurship,Interest.